(untitled) (Global Journal of Human-Social Science, 2015)
This paper is aimed at understanding various planning laws and regulations that serve as hindrance to green economy in Nigerian cities. The study is focused on the horticulture practices in Eti-Osa Local Government Area of Lagos. This is a form of green economy that was not considered during the preparation of the master plan of the area. The survey for the study was conducted on two (2) occasions (2008 and 2013). This was shortly before planning activities became highly intensive during the 6th republic and in the 7th republic. The study purposively sampled all the commercial horticultural gardens available at the two (2) periods; these are 63 and 39 in 2008 and 2013 respectivelyFindings revealed that about 24 (38%) of the gardens has been lost due to strict application of development control regulations in the space of five (5) years. Result also revealed that over N14, 570,000 worth of investment and N11,070,000 annual profit were affected.